2005
DOI: 10.3168/jds.s0022-0302(05)72923-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Feeding, Drinking, and Standing Behavior of Dairy Cows During the Transition Period

Abstract: The aims of this study were to determine how measures of feeding, drinking, and standing behavior change over the period around calving, to derive objective meal and drinking bout criteria for transition cows, and to describe the within-cow consistency of these behavioral measures. Fifteen transition dairy cows were monitored from 10 d before until 10 d after calving. Meal criteria were calculated for each cow in both the pre- and postcalving periods and varied among cows from 5.3 to 105.2 min. There was a ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
151
5
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(190 citation statements)
references
References 24 publications
32
151
5
2
Order By: Relevance
“…In this period mother quickly learns to identify her own calf (Weary & Chua 2000) through the process of maternal grooming and licking (Fraser & Broom 1990) resulting a reciprocal recognition between buffalo dams and their own calves (Usmani et al 1990). The present study reported least eating period in first stage which is in consonance with results observed by Huzzey et al (2005). Immediately after calving during critical period buffalo dam showed least eating time which might be attributed to the fact that buffalo cow spent maximum time in close attachment with their neonate to detect her own calf (Weary & Chua 2000) for better survival.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this period mother quickly learns to identify her own calf (Weary & Chua 2000) through the process of maternal grooming and licking (Fraser & Broom 1990) resulting a reciprocal recognition between buffalo dams and their own calves (Usmani et al 1990). The present study reported least eating period in first stage which is in consonance with results observed by Huzzey et al (2005). Immediately after calving during critical period buffalo dam showed least eating time which might be attributed to the fact that buffalo cow spent maximum time in close attachment with their neonate to detect her own calf (Weary & Chua 2000) for better survival.…”
Section: Discussionsupporting
confidence: 91%
“…Parturition is the most painful process making dam more restless just before the calving. Therefore, majority of cows remain standing before parturition which might be due to discomfort (Huzzey et al 2005). Further, cows have to make physical contact with their new born in order to identify and nurse them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por exemplo, observouse que vacas com maior risco de desenvolver metrite pós-parto apresentaram redução mais severa da duração de comportamento ingestivo nos dias imediatamente anteriores ao parto (URTON et al, 2005). Assim, alterações na ingestão de matéria seca podem ser utilizadas para identificar vacas predispostas a metrite e outras doenças comuns ao período de transição (HUZZEY et al, 2005).…”
Section: Métodos De Diagnóstico De Bem-estar De Bovinos Leiteirosunclassified
“…Drinking activity can be monitored continuously and simultaneously for randomly enrolled cows using a data acquisition system based on an individual radio frequency identification collar (Cardot et al, 2008) or with observers (Jago et al, 2005). Huzzey et al (2005) monitored drinking activity of dairy cows using video cameras connected to a video multiplexer and a time-lapse videocassette recorder. Bewley et al (2008) monitored ruminal temperature using boluses permanently residing in the cow's reticulum and indentified temperatures influenced by drinking events.…”
Section: Introductionmentioning
confidence: 99%